تأثير عدد مستقبلات نظام تحديد المواقع العالميGPS على دقة تعيين نقاط الشبكات الجيوديزية - فايز ديب (Tishreen University, 2017)
تعتبر تقنية نظام تحديد المواقع العالمي GPS وسيلة أساسية في مجال إنشاء الشبكات الجيوديزية. تستخدم الطريقة الساكنة من قياسات نظام تحديد المواقع العالمي GPS بشكل عام في تحديد إحداثيات نقاط الشبكات الجيوديزية. إن تأسيس الشبكات الجيوديزية باستخدام نظام تحديد المواقع العالمي GPS يتطلب تحقيق الدقة والمتانة والاقتصادية. يناقش هذا البحث تأثير طريقة القياس وعدد المستقبلات المستخدمة في دقة تعيين نقاط الشبكات الجيوديزية. تم حساب إحداثيات نقاط شبكة جيوديزية باستخدام جهازي استقبال وثلاثة أجهزة استقبال GPS وبطرق مختلفة مثل الطريقة الشعاعية والمضلعية والشبكية. تمت مقارنة إحداثيات النقاط التي تم الحصول عليها بحالات متعددة. أظهرت الفروقات بين الإحداثيات دقة الطريقة الشبكية في حساب الإحداثيات عند توفر ثلاثة مستقبلات أو أكثر. عند وجود جهازي استقبال فقط تكون الطريقة الشعاعية هي الأفضل من حيث الدقة والموثوقية. GPS technology considers the essential tool for establishing geodetic networks. Static method of GPS is used often in observing geodetic network points. Establishing geodetic networks using GPS requires accuracy, consistency and economency. This paper discusses influence of observation mode and number of GPS receivers in accuracy of calculating of coordinates of points. Coordinates of network points are clculated using tow and three GPS receivers and with diferent methods like radial, traverse, network. Comparison between coordinates for network points obtained by several cases is performed. The differences between coordinates indicate accuracy of network method in calculating coordinates when three or more receivers are avlible. When tow receivers are avilable the radial method is the best in accuracy and consistency.